International Marketing - Baack, Daniel W. (SAGE Publications, Ltd. (UK), 2018)
Now in its second edition, International Marketing continues to provide its trademark integrated approach that explores marketing concepts in depth within a truly international context. The authors discuss five key factors that impact any international marketing venture – culture, language, political/legal systems, economic systems, and technological differences – in relation to the core marketing concepts of markets, products, pricing, distribution (place), and promotion. The book also covers sustainability and bottom-of-the-pyramid issues within each chapter with rich illustrations and examples from both multinational companies and smaller local concerns. New to the second edition: More global focus through new examples, case studies and the experience brought by new co-author, Barbara Czarnecka Brand new chapter on Culture & Cross-Cultural Marketing, including political unrest and the recent return to nationalism (e.g. Brexit and the Trump presidency) and further coverage of developing countries New coverage of digital advances and social media marketing Updated theory and methods, including Service Dominant Logic (S-DL), Consumer Culture Theory (CCT), and Netnography Additional videos supplementing the comprehensive online resource package for students and lecturers A wealth of online resources complement this book. These include a test bank of 50-65 questions per chapter, PowerPoint slides, sample syllabi, interactive maps, country fact sheets, flashcards, SAGE journal articles, and guidelines for developing a marketing plan.